2015
DOI: 10.1021/acs.jpcb.5b09052
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of Ice Nucleation by Kaolinite (001) with Rigid and Flexible Surfaces

Abstract: Nucleation of ice by airborne particles is a process vital to weather and climate, yet our understanding of the mechanisms underlying this process is limited. Kaolinite is a clay that is a significant component of airborne particles and is an effective ice nucleus. Despite receiving considerable attention, the microscopic mechanism(s) by which kaolinite nucleates ice is not known. We report molecular dynamics simulations of heterogeneous ice nucleation by kaolinite (001) surfaces. Both the Al-surface and the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
175
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(196 citation statements)
references
References 46 publications
20
175
1
Order By: Relevance
“…The CLAYFF force field (Cygan et al 2004) was adopted to define all bonded and non-bonded interaction parameters of kaolinite surface. A bread usage of the Pavese and CLAYFF forcefields can be found in recent literature adoptions (Fazelabdolabadi and Alizadeh-Mojarad 2016;Ghatee et al 2015;Greathouse et al 2015;Keller et al 2015;Zielke et al 2015). In case of f10 14g calcite, the methodology suggested by Headen and Boek (2011) was used to describe the van der Waals interaction parameters (to model fluid-solid interface).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CLAYFF force field (Cygan et al 2004) was adopted to define all bonded and non-bonded interaction parameters of kaolinite surface. A bread usage of the Pavese and CLAYFF forcefields can be found in recent literature adoptions (Fazelabdolabadi and Alizadeh-Mojarad 2016;Ghatee et al 2015;Greathouse et al 2015;Keller et al 2015;Zielke et al 2015). In case of f10 14g calcite, the methodology suggested by Headen and Boek (2011) was used to describe the van der Waals interaction parameters (to model fluid-solid interface).…”
Section: Methodsmentioning
confidence: 99%
“…A few investigations were also directed towards analysis of adsorption of organic molecules over clay (Hu et al 2014;Pernyeszi et al 1998;Wang et al 2013) (mainly kaolinite), as well as non-clay (Cooke et al 2010;de Leeuw and Parker 1998;Freeman et al 2009;Guiwu et al 2009;Keller et al 2015;Sakuma et al 2014) (mainly calcite) surfaces. In this regards, the main focus has been devoted to the {001} kaolinite or {1014} calcite structures, on the premise of holding the primary cleavage planes (Miller et al 2007;Sekkal and Zaoui 2013;Titiloye et al 1993;Zielke et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Adsorbed water on the octahedral Al-OH surface exhibits hexagonal patterns but no close lattice match with ice (Croteau et al, 2008(Croteau et al, , 2010. Simulations by Zielke et al (2016) showed that for the Al surface, reorientation of the surface hydroxyl groups is essential for ice nucleation. On the siloxane surface, ice nucleates via an ordered arrangement of hexagonal and cubic ice layers, joined at their basal planes, where the interfacial energy cost is low.…”
Section: Kaolinitementioning
confidence: 99%
“…This concept has been discussed in Ochshan and Cantrell (2006), and more recently in Zielke et al (2015). This theory involves the movement of molecules at the surface of both the IN and the water droplet.…”
Section: Peanut Butter 2500mentioning
confidence: 99%